Study on the Evolution Law of Fracture Field in Full-Mechanized Caving Mining of Double System and Extrathick Coal Seam - Feng Du; Wenqiang Wang; Zhenhua Li (Advances in Civil Engineering)
During the full-mechanized caving mining, the overburden strata in the double system and extrathick coal seam of the Datong mining area are largely damaged. Water and harmful gas in the old goaf may be discharged when overburden fractures evolve to the upper goaf, which poses a major threat to the normal production of the panel. To study the movement of overburden strata and the evolution of fracture field under the full-mechanized caving mining of the double system and extrathick coal seam, panel 8309 of Tongxin mine was taken as the research object; the evolution rule of fracture field in the full-mechanized caving mining of the double system and extrathick coal seam was obtained through field measurement and physical similar simulation. The results show the following: (1) the far-field and near-field key strata play a decisive role in controlling the fracture evolution of overburden strata. When the far-field key strata break and the development height of fractures reaches 220.9 m, panel 8309 is connected with the overburden goaf. (2) Based on the “O-shape circle” theory of mining fracture, with the continuous advance of the panel, the overburden breaks periodically, and a “fracture surface” with a certain angle of 61°–67° can be formed along with the advancing direction of the panel. (3) When the key strata are broken and the development height of fractures reaches the maximum, the fracture surface is formed as the “main fracture surface,” which is the only downward discharge pathway for goaf water and harmful gas. The overall shape fracture surface is “inverted trapezoid” in the upper part and “positive trapezoid” in the lower part. (4) Based on the field measurement of the water level of borehole and the observation of mine pressure, the correctness of the evolution law of the similar simulated fracture field is verified.